2017
DOI: 10.1002/adma.201607039
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics and Morphology Control of Formamidinium–Cesium Mixed‐Cation Lead Mixed‐Halide Perovskite via Tunability of the Colloidal Precursor Solution

Abstract: spin-coating, [2,3] two-step interdiffusion, [4] dip-coating, [4] inkjet printing, [5,6] and spray pyrolysis. [7] These solution-based fabrication methods of perovskite films have been used in a variety of devices ranging from field-effect transistors, [8] light-emitting devices (LED), [9] photodetectors, [10,11] to solar cells. [2][3][4]12] Although most perovskite thin films are fabricated using a saltbased precursor solution, little effort has been dedicated to characterizing the structure and time-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
236
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(244 citation statements)
references
References 46 publications
7
236
0
1
Order By: Relevance
“…[21,22] More recently, we have demonstrated ptype doping of the perovskite surface, which is an additional route to suppressing recombi nation at the perovskite/holetransport material interface. [15,32] Examples of this are: solvent mixtures, and the addition of amines, acids, or excess ammonium halides to the precursor solution. [15,32] Examples of this are: solvent mixtures, and the addition of amines, acids, or excess ammonium halides to the precursor solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,22] More recently, we have demonstrated ptype doping of the perovskite surface, which is an additional route to suppressing recombi nation at the perovskite/holetransport material interface. [15,32] Examples of this are: solvent mixtures, and the addition of amines, acids, or excess ammonium halides to the precursor solution. [15,32] Examples of this are: solvent mixtures, and the addition of amines, acids, or excess ammonium halides to the precursor solution.…”
Section: Introductionmentioning
confidence: 99%
“…[24] In cases where a "passivating" agent is added directly to the precursor solution, the resulting improvement in the optoelec tronic properties of the film is often due to the additive medi ating crystallization such that the resulting film has fewer grain boundaries and surface defects, for example, through altering the size and concentration of colloids in the solution. [15,[32][33][34][35] Improvements in the device performance have also been achieved by changing the electron selective layers in the device stack. [15,[32][33][34][35] Improvements in the device performance have also been achieved by changing the electron selective layers in the device stack.…”
Section: Introductionmentioning
confidence: 99%
“…[17] As olution of FA 0.75 MA 0.25 SnI 3 in DMSO was used as the precursor and the spin coating was performed at 5000 rpm for 100 s. Thec hlorobenzene (Ph-Cl) antisolvent was dropped onto the spinning film at the 63 s mark to promote faster crystallization and the perovskite film was afterwards annealed at 100 8 8C. [28][29][30][31][32][33][34] With the stable Pb intermediate states serving as nucleation centers,c rystal growth is retarded under room temperature,e nabling am ore controllable film formation process. 10 mol %ofSnF 2 was added in the precursor to stabilize the Sn perovskite and to prevent oxidation.…”
mentioning
confidence: 99%
“…Thee ntire process was performed under Ar atmosphere.D etails of the method can be found in the supporting information. [29][30][31][32][33][34] Instead, for Sn-based perovskite,w es uggest that the small perovskite crystals serving as nucleation centers form immediately after antisolvent dripping.T he proposed mechanism is shown in Figure 2. [14] Thef ilm color turned from transparent to dark brown immediately after antisolvent dripping, but faded to at ransparent film again before the spinning was stopped at 100 s( Figure S2a).…”
mentioning
confidence: 99%
“…Moore et al [10] , Yan et al [19] , and later extended by Hu et al [20] and McMeekin et al [21] showed that lead polyhalide and lead salt colloidal particles played a role in crystallization growth and morphology for both simple methylammonium lead triiodide as well as mixed-cation varieties in DMF and DMSO systems. Moore et al [10] , Yan et al [19] , and later extended by Hu et al [20] and McMeekin et al [21] showed that lead polyhalide and lead salt colloidal particles played a role in crystallization growth and morphology for both simple methylammonium lead triiodide as well as mixed-cation varieties in DMF and DMSO systems.…”
Section: Solution Processingmentioning
confidence: 97%